On the Cutting Edge: Wound Care for the Endovascular Specialist - Olivieri, Brandon; Yates, Timothy E.; Vianna, Sofia; Adenikinju, Omosalewa; Beasley, Robert E.; Houseworth, Jon (Seminars in Interventional Radiology, 2018)
Clinical outcomes in patients with critical limb ischemia (CLI) depend not only on endovascular restoration of macrovascular blood flow but also on aggressive periprocedural wound care. Education about this area of CLI therapy is essential not only to maximize the benefits of endovascular therapy but also to facilitate participation in the multidisciplinary care crucial to attaining limb salvage. In this article, we review the advances in wound care products and therapies that have granted the wound care specialist the ability to heal previously nonhealing wounds. We provide a primer on the basic science behind wound healing and the pathogenesis of ischemic wounds, familiarize the reader with methods of tissue viability assessment, and provide an overview of wound debridement techniques, dressings, hyperbaric therapy, and tissue offloading devices. Lastly, we explore emerging technology on the horizons of wound care.
Keywords: critical limb ischemia; wound care; ulcer; debridement; peripheral arterial disease; interventional radiology